Implementasi Desain Interior Mandarin Chinese Restaurant “The Fortune Chinese” - Hanapiah, Dio Pratama; H. Istanto, Freddy; Nuradhi, L. Maureen (KREASI, 2016)
Balikpapan is one of many cities in Indonesia which has significant development through this past years. One of outstanding business industry nowdays is property, as a result of increasing population in the city. Therefore, the demand for interior design’s service will increase steadily along with the growing property’s industry. In conclusion, based on the high demand for interior design’s service in Balikpapan, Pratama Interior Consultant as an interior design’s company has great chance and opportunity to establish developing company, providing such service for the needs of the market. Pratama Interior Consultant as an interior design’s company specialized in scope of projects for residential, commercial and hospitality design. Pratama Interior Consultant has commitment in providing excellent service to solve project’s needs. Mandarin Chinese Restaurant is a restaurant located in Balikpapan. The restaurant serves Chinese culinary dish. This restaurant’s capacity for 350 persons with 150 persons on the1st floor and the rest on the 2nd floor. The restaurant’s segment is people with middle to high income. The design’s concept to be applied for the restaurant is Fortune Chinese, hoping the customer will directly feel the Chinese atmosphere through the interior design. The interior elements of the floor, wall, ceiling, and also the furniture help build the ambience of Chinese and altogether brings the whole concept in harmony.